Enhanced Active Voltage Regulation Capability for Three-Level NPC Converters with the Space Vector Modulation Method - Huang, Zhen; Wang, Jingyi; Zhang, Shuhao; Zhu, Rui; Guo, Feng; Xia, Yonghong (Journal of electrical engineering & technology, 2025)
The performance of three-level neutral point clamped (NPC) converters is subject to the neutral point (NP) voltage balancing. Thus, the active voltage regulation capability of NP voltage is crucially required for NPC converters. In this paper, an active space vector modulation strategy is proposed. It accurately utilizes the amount of zero-level duty cycle adjustment in a switching cycle, which can actively control the NP voltage along with the reduced capacitor voltage ripple. Besides, the switching states associated with low common mode voltage (CMV) are selected for the addressed modulation strategy. Compared with the conventional space vector pulse width modulation, the proposed method exhibits faster response, lower CMV, and capacitor ripple in achieving NP voltage balance. Finally, the given experimental results have proven the feasibility and effectiveness of the proposed modulation strategy.